2023
DOI: 10.3390/jmse11071463
|View full text |Cite
|
Sign up to set email alerts
|

The Clay Mineralogy and Geochemistry of Sediments in the Beibu Gulf, South China Sea: A Record of the Holocene Sedimentary Environmental Change

Abstract: In this study, we analyzed the clay mineralogy and geochemistry of surface and drill core samples from the northeastern Beibu Gulf in order to unravel the sediment provenance of, and factors controlling, the sedimentary environment. The main clay mineral assemblage in the surface sediment samples included kaolinite (27–72%), smectite (4–51%), illite (7–20%), and chlorite (8–17%). The study area comprises three major clay distribution zones (from the northeastern coastal area to central Beibu Gulf basin), i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…This helps to understand the formation and distribution of marine clays. Guan et al [58] found that low sedimentation rates and hydrodynamic perturbations have a greater impact on sedimentary processes in marine clays than climatic fluctuations.…”
Section: Marine Claymentioning
confidence: 99%
“…This helps to understand the formation and distribution of marine clays. Guan et al [58] found that low sedimentation rates and hydrodynamic perturbations have a greater impact on sedimentary processes in marine clays than climatic fluctuations.…”
Section: Marine Claymentioning
confidence: 99%